ANALISIS PINJAMAN ONLINE DALAM PERSPEKTIF HUKUM ISLAM: ANTARA RIBA DAN GHARAR - Efendi, Efendi (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Online loans can be an important tool in meeting economic needs, it is very important for Muslims to find solutions that are not only practical, but also halal in accordance with Islamic law. This research uses the library research method, where the main source analyzed is scientific literature relevant to the topic, such as journal articles, research reports, and legal documents. The results of the study show that, 1). The view of Islamic law on the concept of riba applied in online loans is that riba is expressly prohibited because it is considered a form of exploitation and injustice. In the context of online loans, riba often appears in the form of high interest charged to borrowers, thus burdening them and unfairly benefiting the lender. 2). Islamic law’s view of the uncertainty aspect (gharar) in an online loan agreement is that gharar refers to uncertainty or ambiguity in a transaction that can cause losses to one of the parties. In the context of online loans, gharar can arise if the terms and conditions in the agreement are not clearly stated, for example regarding additional fees, interest, or hidden fines. 3). The role of government regulation and Islamic financial institutions in online loan services from the perspective of Islamic legal principles is that the government and Islamic financial institutions have an important role in ensuring that online loan services run in accordance with Islamic principles. Islamic financial institutions offer financing alternatives that are in accordance with Islamic law, such as interest-free loans (qardh hasan) or profit-sharing systems (mudharabah/musyarakah)